Penegakan Sanksi Administrasi Terhadap pelanggaran Parkir Di Kota Ambon - Peea, Stelward Excel; Mustamu, Julista; Saija, Vica Jilliyan Edsti (Jurnal Saniri, 2024)
Illegal parking is a phenomenon in which the act of parking is done illegally or unofficially with unilateral recognition of the parking area. The purpose of this article is to find out and analyze sanctions and the application of sanctions against illegal parking in Ambon City. This research uses a Normative Juridical approach, in data collection the emphasis is on primary and secondary data sources, aimed at a case approach. Based on research regarding the application of administrative sanctions to illegal parking in the city of Ambon, it can be seen that the sanctions that can be used in handling illegal parking are punitive sanctions, which means that sanctions aimed at a violator are in the form of written warnings, revocation of certain permits, and administrative fines. The application of administrative sanctions for parking violations in Ambon City is still not enough to make Ambon City a city free of illegal parking, the sanctions applied by the Ambon City government have not had a deterrent effect on parking violators. This is due to a lack of supervision and control carried out by the authorities or the Ambon City Transportation Service.